The Spillover Effects of Investment, Economic Growth and Electricity Consumption: An Application Mathematical Dynamic Industry-Related Models Approach - Hong, Cheng-Yih; Yen, Yu-Shuang; Lee, Tsai-Rong (International Journal of Energy Economics and Policy, 2019)
The economic growth pattern of investment has been proved in Asian countries, but it often falls into development bottleneck after the economy develops to a certain extent, especially in countries with lack of resources. One of the important reasons is the supply of energy and electricity. Establishing a sustainable development path requires thinking about economic development and environmental protection at the same time. This will face how to establish a balanced industrial structure and a stable electricity supply system, and investment in production equipment and R&D will be an indispensable factor. R & D investment and equipment investment contribute to economic growth. This study employs a dynamic industry-related model to estimate the economic spillover effect from both R&D investment and equipment investment. The present study attempts to measure (1) the difference in the investment multiplier of R&D investment and equipment investment, (2) the difference in the employment creation effect of investment R&D and equipment investment. Analysis of future industrial development strategies needs to consider energy and electricity consumption. This study will estimate (3) the impact of equipment investment and R&D investment on power consumption, and compare the differences between the two on the industry. This study uses mathematical dynamic industry-related models to estimate (1) ~ (3) and found that different investment methods will make the inter-industry economy have different spillover effects, and also show different demand in power consumption. Keywords: R&D investment; equipment investment; dynamic industry-related model; electricity consumption JEL Classifications: C60ï¼›O30ï¼›Q43ï¼›Q56 DOI: https://doi.org/10.32479/ijeep.7584